Diagnostics As A Precondition Of Value Orientation In Primary School - Yeganyan, Gayane; Harutyunyan, Gayane (Զանգակ հրատ.)
The demands put forward the contemporary primary school are being changed year by year due to a number of factors - political, socio-economic, cultural, etc. Nowadays, when there are confusion and a struggle for values around the world, every nation must strive to recognize and preserve its ethnic moral values in harmony with contemporary demands. The purpose of contemporary education is not limited by equipping the individual with knowledge and skills, but also to develop the certain moral qualities, and one of the most important functions of a teacher is to shape the worldview of students. The pedagogical diagnostics with its rich toolkit, a wide selection of methods and methodology, is a prerequisite for value orientation in the elementary school and contributes to the formation of the primary schooler value system of significant values important for the individual and society.
Keywords: Pedagogy